2012
DOI: 10.1002/ijc.27667
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐associated autoantibody signature for the early detection of gastric cancer

Abstract: Autoantibodies against tumor-associated antigens are very attractive biomarkers for the development of noninvasive serological tests for the early detection of cancer because of their specificity and stability in the sera. In our study, we applied T7 phage display-based serological analysis of recombinant cDNA expression libraries technique to identify a representative set of antigens eliciting humoral responses in patients with gastric cancer (GC), produced phage-antigen microarrays and exploited them for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 44 publications
6
78
0
Order By: Relevance
“…In patients with earlystage NPC, use of the autoantibody panel provided a better diagnostic efficacy (Table 3). This indicates that the autoantibody panel may be a promising marker for the early detection of NPC and that the induction of autoantibodies occurs early in the process of carcinogenesis, which is consistent with previous studies (9)(10)(11)(12)(13)(14)(15)(16)(17). Analysis of VCA-IgA presented here is also shown to be a useful diagnostic biomarker of NPC, which is in agreement with a study by Ai and colleagues (21), but the high false-negative rates will prevent the timely diagnosis of NPC patients in endemic areas, particularly the symptomless, early-stage patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In patients with earlystage NPC, use of the autoantibody panel provided a better diagnostic efficacy (Table 3). This indicates that the autoantibody panel may be a promising marker for the early detection of NPC and that the induction of autoantibodies occurs early in the process of carcinogenesis, which is consistent with previous studies (9)(10)(11)(12)(13)(14)(15)(16)(17). Analysis of VCA-IgA presented here is also shown to be a useful diagnostic biomarker of NPC, which is in agreement with a study by Ai and colleagues (21), but the high false-negative rates will prevent the timely diagnosis of NPC patients in endemic areas, particularly the symptomless, early-stage patients.…”
Section: Discussionsupporting
confidence: 80%
“…Autoantibodies have attracted more attention as possible biomarkers in recent years. A large number of studies describe the presence of autoantibodies to tumorassociated antigens (TAA) in serum samples from patients with a variety of cancers (9)(10)(11)(12)(13)(14)(15). Interestingly, autoantibodies seem to appear months to years before the clinical diagnosis of a tumor, which makes measurement of autoantibodies suitable for earlystage cancer diagnosis (9,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The authors of the systematic review note that in cases where autoantibodies were combined into multiplexed panel assays, substantially higher sensitivity at reasonably high levels of specificity could be achieved. One such attempt by Zayakin et al [60] produced a 45-autoantibody signature that discriminated between gastric cancer and healthy controls with an area under the curve of 0.79 (59% sensitivity and 90% specificity).…”
Section: Diagnostic Biomarkersmentioning
confidence: 98%
“…Cancer-specific autoantibody signatures with diagnostic relevance have been identified in a variety of solid cancers, including prostate, lung, breast, ovarian and gastric cancer [4,6,[26][27][28]. Several of these studies demonstrated that cancer-testis antigens (CTAs) -antigens that are normally expressed only in germ line cells and aberrantly expressed in a wide range of cancer types, are among the most frequent autoantibody targets and therefore are of the highest diagnostic value [14].…”
Section: Introductionmentioning
confidence: 98%